Exploring the lived experience of endoscopy trainees and their perceptions of nurse endoscopists as trainers. (1st October 2021) - Donnelly, Leigh; Steven, Alison
Abstract : Background: UK endoscopy services face considerable workforce pressures from an increasing demand for procedures. To meet this need, health services have introduced the role of nurse endoscopist (also known as clinical, non-medical or non-physician endoscopist). These roles have grown and developed to include performing many complex diagnostic and therapeutic procedures, as well as the provision of endoscopy training. Aims: This study examines the lived experiences of (nurse and medical) endoscopy trainees, especially regarding being trained by nurse endoscopists. Methods: The study employed interpretive phenomenological analysis (IPA). Data were collected through semi-structured in-depth interviews of 10 participants, who were selected from a sample of trainees attending a basic colonoscopy skills course. Interviews were preceded by observations to gain contextual insights into the training experience. The data were analysed in stages through a process of reading and re-reading the transcripts, making initial descriptive observations and then annotating with discursive, linguistic and conceptual comments. Findings: Four emerging themes were identified. A lack self-confidence was a barrier to progression, compounded by the emotional impact of making mistakes without comprehensible constructive feedback. Attitudes of trainers and other endoscopy staff, as well as their relationships with trainees, had an impact on self-confidence and educational experience. Pressure on endoscopy units to perform procedures led to a tendency to treat training like a burden, although training was seen as an important investment. Trainees sought to differentiate nurse endoscopist and medical endoscopist roles and justify their skills and value, with comparisons between different nurse and medical trainers. Conclusion: The emerging themes illustrate the requirement for a collegiate approach to endoscopy training.